2021
DOI: 10.1123/jpah.2020-0844
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Fitness, School Readiness, and Cognition in Early Childhood: A Systematic Review

Abstract: Background: Early childhood is an important age for brain and cognitive development. Given the support of physical activity and fitness on cognition and academic performance in older children, more research has emerged recently focusing on younger children. In this systematic review, the authors review the relations between physical activity/fitness and academic-related (ie, school readiness and cognitive) outcomes in early childhood. Methods: A search was conducted from PubMed, PsycINFO, Web of Science, ERIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 99 publications
1
23
1
Order By: Relevance
“…These guidelines highlight the importance of physical activity in preschool aged children, however, to date, studies exploring the link between physical activity and cognitive outcomes lacks consensus [7]. One possible reason for the mixed findings may be that studies using objective measures of physical activity do not consider if the relationship between physical activity and cognitive outcomes varies by the intensity of physical activity (e.g., MVPA vs. total physical activity).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These guidelines highlight the importance of physical activity in preschool aged children, however, to date, studies exploring the link between physical activity and cognitive outcomes lacks consensus [7]. One possible reason for the mixed findings may be that studies using objective measures of physical activity do not consider if the relationship between physical activity and cognitive outcomes varies by the intensity of physical activity (e.g., MVPA vs. total physical activity).…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for the mixed findings may be that studies using objective measures of physical activity do not consider if the relationship between physical activity and cognitive outcomes varies by the intensity of physical activity (e.g., MVPA vs. total physical activity). A deeper understanding of the type and intensity of physical activity that positively impacts developmental outcomes in preschool children will contribute towards a better understanding of the pathways through which physical activity influences a young child's development, particularly their cognitive development [7]. Such information is needed to better inform the design of future physical activity intervention studies to better support young children's cognitive development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it focusses on the control, coordination and quality of motor skills, such as hopping and skipping [4]. This finding is supported by a recent systematic review [46], which found no clear consensus on the role of PA for academic outcomes in early childhood. Furthermore, it may also be possible that children who engage in higher levels of PA do less sedentary activities, which may be perceived as better for the development of school readiness, such as reading, writing, fine motor activities, socialising and communicating.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of positive associations between physical activity (PA) and cognitive function in school-aged children and youth; however, evidence on associations for PA with academic achievement is inconsistent ( Rasberry et al, 2011 ; Donnelly et al, 2016 ). In younger children, the evidence on associations for PA with cognition and learning is weaker and overall less consistent ( Timmons et al, 2012 ; Carson et al, 2016 , 2017 ; Wood et al, 2020 ; St. Laurent et al, 2021 ). Yet, the preschool years are crucial with respect to developing cognitive skills ( Thompson and Nelson, 2001 ; Diamond, 2006 ; Calkins, 2007 ; Eisenberg and Zhou, 2016 ).…”
Section: Introductionmentioning
confidence: 97%